0838 Clinical and Patient Global Impression in a Phase 2/3 Study of Sodium Oxybate in Children and Adolescents with Narcolepsy with Cataplexy. (27th April 2018) - Ruoff, C; Simakajornboon, N; Hassan, F; Chen, M; Swick, T; Black, J; Wang, Y; Parvataneni, R; Plazzi, G
Abstract: Introduction: Clinical and Patient Global Impression (CGI and PGI, respectively) for cataplexy severity and overall narcolepsy symptoms, including excessive daytime sleepiness, were assessed as secondary/exploratory endpoints, respectively, in a phase 2/3, multicenter study of sodium oxybate (SXB) in pediatric patients with narcolepsy with cataplexy. Methods: Children and adolescents (7–16 years) diagnosed with narcolepsy with cataplexy who were either treated or untreated with SXB at enrollment were included. Untreated participants were titrated to a stable dose (SD) of SXB; SXB-treated participants remained on their current dose. After the SD period, participants entered a 2-week, double-blind, placebo-controlled withdrawal period (DB) and were randomized to continue SXB (at SD) or receive placebo. At the end of the DB period, CGI for cataplexy severity, and CGI and PGI for overall narcolepsy symptoms were assessed and compared with scores at the end of the SD period. Overall scores from 3 (Very Much Improved) to -3 (Very Much Worse) were compared between treatments using the Cochran-Mantel-Haenszel test for row mean score differences. Treatment emergent adverse events (TEAEs) were assessed. Results: Sixty-three participants were randomized (female: 44%; SXB-naïve: 62%). At study entry, the mean CGI score for cataplexy severity and overall symptoms corresponded to "moderately ill." At the end of the DB period, the placebo group demonstrated statistically significant worsening in both CGI and PGI: mean change (standard deviation) CGI for cataplexy severity, placebo -1.5 (1.19) vs SXB -0.4 (1.12) ( P =0.0006); mean change CGI for overall narcolepsy symptoms, placebo -1.4 (1.13) vs SXB -0.4 (0.95) ( P =0.0008); and mean change PGI for overall symptoms, placebo -1.3 (0.97) vs SXB 0.0 (1.30) ( P =0.0001). The most frequently reported TEAEs (>10%) were enuresis, nausea, vomiting, headache, and weight decrease. Conclusion: Randomization to placebo relative to continuation of SXB resulted in significant worsening of cataplexy severity and overall narcolepsy condition as rated by clinicians and participants. These results support the efficacy of SXB on narcolepsy symptoms, including cataplexy, in pediatric patients with narcolepsy with cataplexy. Support (If Any): Jazz Pharmaceuticals.